A web‐based tailored nursing intervention (TAVIE en m@rche) aimed at increasing walking after an acute coronary syndrome: Multicentre randomized trial. (7th August 2019) - Kayser, John William; Cossette, Sylvie; Côté, José; Tanguay, Jean‐Francois; Tremblay, Jean‐Francois; Diodati, Jean Gino; Bourbonnais, Anne; Purden, Margaret; Juneau, Martin; Terrier, Julien; Dupuis, Jocelyn; Maheu‐Cadotte, Marc‐André; et al.
Abstract: Aim: Evaluate a web‐based tailored nursing intervention, TAVIE en m@rche, on increasing daily steps after an acute coronary syndrome. Design: Parallel two‐group multicentre randomized trial. Methods: An experimental group receiving TAVIE en m@rche, was compared to  a control group receiving hyperlinks to public websites. Acute coronary syndrome patients who were insufficiently active were recruited from three coronary care units. Daily steps at 12 weeks were the primary outcome. Secondary outcomes included self‐reported walking and moderate to vigorous physical activity (MVPA). Exploratory outcomes were angina frequency, emergency department visits, hospitalizations and secondary prevention programme attendance. Results: Primary data were analysed for 39 participants. No significant effects were found. At 12 weeks 275.9 more daily steps and 1, 464.3 more energy expenditure in MVPA were found in the experimental group relative to the control. No effects were found for angina frequency, emergency department visits, hospitalizations and secondary prevention programme attendance. Conclusion: The lack of effect on our primary result may be explained by the intervention goal that was mismatched to the needs of our mostly sufficiently active sample at randomization, resulting in no meaningful change in daily steps. Although the non‐significantly greater increase in self‐reported MVPA may represent gains in health among the participants that accessed TAVIE en m@rche, this result should be interpreted with caution. Impact: From 40%‐60% of acute coronary syndrome patients self‐report insufficient levels of physical activity. No effect was found on the primary outcome of daily steps. Although not significant, a greater increase in MVPA was found at 12 weeks. The primary outcome can be explained by most of the sample having attained the physical activity recommendation at randomization. Caution in interpreting the non‐significant increase in MVPA is warranted due to attrition bias and statistical uncertainty. Future directions may consider the timing of randomization in relation to meeting the needs of insufficiently active acute coronary syndrome patients. Abstract : 目的: 评估基于网络的定制护理干预(TAVIE en m@rche)对于急性冠脉综合征后增加每日行走步数的作用。 设计: 平行的两组多中心随机研究 方法: 对比接受TAVIE en m @ rche的实验组与接收公共网站超链接的对照组。我们从三个冠心病重症监护病房招募了活动不足的急性冠状动脉综合征患者。研究主要结果是12周的每日步数。次要结果包括患者自己报告的行走和中等强度到高强度的身体活动(MVPA)。探索性结果为心绞痛发作频率、急诊就诊、住院和二级预防方案出现次数。 结果: 我们分析了39名参与者的原始数据, 没有发现显著影响。在十二周中, 相比于对照组, 实验组的中等强度到高强度的身体活动中, 每日步数增加了275.9步, 并且增加了1464.3的能量消耗。心绞痛发作频率、急诊就诊、住院和二级预防方案出现次数没有受到影响。 结论: 没有对主要结果产生影响的原因可能是干预目标与随机分配的多数活动充分的样本需求不匹配, 导致每日步数没有出现有意义的变化。尽管患者自己报告的中等强度到高强度的身体活动并没有显著地大幅增长, 这可能意味着访问TAVIE en m@rche的参与者健康状况有所改善, 但是对于这一结果, 应当谨慎解释。 影响: 40%至60%的急性冠状动脉综合征患者自己报告的身体活动不足。每日步行没有对主要结果产生影响。尽管不显著, 但在十二周中, 每日中等强度到高强度的身体活动有所增长。出现这样的主要结果的原因是, 大多数样本在随机分组时已经得到了活动身体的建议。由于损耗性偏差和统计不确定性, 对这一非显著增长, 应当谨慎解释。今后的研究方向可能会考虑随机化的时间, 以满足缺少身体活动的急性冠状动脉综合征患者的需求。